Impending sepsis-induced coagulopathy (SIC) is associated with increased disease severity in SIC-negative patients: a secondary analysis of a prospective exploratory study - Schmoch, Thomas; Möhnle, Patrick; Nusshag, Christian; Feisst, Manuel; Weigand, Markus A.; Brenner, Thorsten (Frontiers in Medicine, 2025)
Due to the intense crosstalk between the coagulation and immune systems, coagulation disorders are an integral part of the disturbed host response to infection that defines sepsis. These so-called sepsis-induced coagulopathies (SIC) are associated with increased morbidity and mortality. However, we still do not know enough about the prevalence and risk factors for SIC in different patient groups. In this study, we present a secondary analysis of a prospective, observational study. The objectives of this secondary analysis were (1) to estimate the prevalence of SIC at the onset of sepsis, (2) to assess the prevalence of SIC throughout the intensive care unit (ICU) stay using a previously described modified SIC score, and (3) to evaluate the association between SIC and morbidity and mortality. The prevalence of SIC at the onset of sepsis was 15.0% (95% confidence interval [CI]: 9.3–23.3%). A total of 24 additional patients who were SIC-negative at the onset of sepsis developed SIC according to the modified SIC score during their ICU stay. In total, we estimated that 39.0% (95% CI: 30.0–48.8%) of patients experienced relevant SIC during their ICU stay. Septic shock, a high lactate level, and a high Sequential Organ Failure Assessment (SOFA) score at the onset of sepsis in SIC-negative patients were associated with SIC development during the course of the disease. These findings need to be verified in larger cohorts and may represent a starting point for the development of a new screening tool for the identification of patients with sepsis at high risk of developing SIC.